New approaches to bedside monitoring in stroke. (August 2012) - Cyrous, Alma; O'Neal, Brandon; Freeman, W David
Stroke is a common, potentially devastating disease with potential high morbidity and mortality. Recognition at the onset of acute ischemic stroke is pivotal to changing outcomes such as intravenous thrombolysis. Stroke monitoring is a burgeoning field with various methods described and newer devices that aid in detecting acute or worsening ischemia that can lead to improved bedside and intensive care unit management. This article describes various methods of bedside stroke monitoring including newer techniques of intracranial pressure monitoring using the pressure reactivity index and compensatory reserve index to detect changes in autoregulatory states, noninvasive intracranial pressure monitoring, quantitative EEG with alpha–delta ratio, transcranial Doppler, methods of arteriovenous brain oxygen monitoring such as jugular venous oxygen and near-infrared spectroscopy, invasive brain oxygen probes such as Licox™ (brain tissue O2 ), cerebral blood flow probe (CBF Hemedex™) and cerebral microdialysis.